Diagnostic methods and surgical treatment of patients with thoracoabdominal traumas (review of the literature) - Ogli Yahyoev, Sardorbek; Minkhodzhievich Khodzhimatov, Gulomidin (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Thoracoabdominal traumatism is a topical problem of modern medicine due to its wide prevalence, severe course and unfavorable outcome. This article presents an overview of the epidemiology, diagnosis, and surgical treatment of patients with thoracoabdominal injuries. It showed that the current incidence of thoracoabdominal injuries reaches 13.7–16.4% of all chest and abdominal injuries. Lethality in thoracoabdominal injuries ranges from 3.13% to 20%. In most cases these are patients of working age, with an average age of 27.5–34.8 years, men comprising 71.2%. Nowadays, the number of patients with thoracoabdominal injuries tends to increase in Uzbekistan and other economically developing countries of the world because of increasing transportation, construction and crime. Video-thoracoscopy and video-laparoscopy are among the widespread methods of diagnosis and treatment of thoracoabdominal traumas. According to many authors, the specificity of video-laparoscopy and video-thoracoscopy is 100%, and the sensitivity is 87.5–99.3%.